A STUDY ON SELF COMPACTING CONCRETE AND ORDINARY CONCRETE WITH RICE HUSK ASH AS A PARTIAL REPLACEMENT FOR CEMENT - Devi, B.Brinda; sureshkumar, R. (IJRDO - Journal of Mechanical And Civil Engineering, 2015)
This paper presents a review on self compacting concrete and ordinary concrete with RHA (Rice husk ash) as a partial replacement of cement, due to the high increase in construction which has brought a heavy demand for ingredients of concrete such as cement and sand, and these materials are becoming costly and scarce. Rice Husk ash is a waste material its use in the production of concrete may prove to be advantageous in an agriculture driven economy like India. It has been used as a highly reactive pozzolanic material to improve the microstructure of the interfacial transition zone (ITZ) between the cement paste and the aggregate in self-compacting concrete. The basic objective of the study is to understand the strength characteristics of the selfcompaction mixes with different compositions of RHA ( 5% 7.5% 10% 12.5% 15%) and are compared with conventional concrete. Various specimens were tested for compressive, split tensile and flexural strength of self-compacting concrete and ordinary concrete incorporating various percentage of rice husk ash.